Universal Voltage Conveyor and its Novel Dual-Output Fully-Cascadable VM APF Application - Herencsár, Norbert; Koton, Jaroslav; Hanák, Pavel (MDPI, 2017)
This letter presents a novel realization of a voltage-mode (VM) first-order all-pass filter (APF) with attractive features. The proposed circuit employs a single readily available six-terminal active device called as universal voltage conveyor (UVC) and only grounded passive components, which predict its easy monolithic integration with desired circuit simplicity. The auxiliary voltage input (W) and output (ZP, ZN) terminals of the device fully ensure easy cascadability of VM APF, since the input and output terminal impedances are theoretically infinitely high and zero, respectively. Moreover, thanks to mutually inverse outputs of the UVC, the proposed filter simultaneously provides both inverting and non-inverting outputs from the same configuration. All of these features make the UVC a unique active device currently available in the literature. The behavior of the filter was experimentally measured using the readily available UVC-N1C 0520 chip, which was produced in cooperation with ON Semiconductor Czech Republic, Ltd.

This letter presents a novel realization of a voltage-mode (VM) first-order all-pass filter (APF) with attractive features. The proposed circuit employs a single readily available six-terminal active device called as universal voltage conveyor (UVC) and only grounded passive components, which predict its easy monolithic integration with desired circuit simplicity. The auxiliary voltage input (W) and output (ZP, ZN) terminals of the device fully ensure easy cascadability of VM APF, since the input and output terminal impedances are theoretically infinitely high and zero, respectively. Moreover, thanks to mutually inverse outputs of the UVC, the proposed filter simultaneously provides both inverting and non-inverting outputs from the same configuration. All of these features make the UVC a unique active device currently available in the literature. The behavior of the filter was experimentally measured using the readily available UVC-N1C 0520 chip, which was produced in cooperation with ON Semiconductor Czech Republic, Ltd.
Universal Voltage Conveyor and its Novel Dual-Output Fully-Cascadable VM APF Application
Keywords: active circuit; all-pass filter; dual-output; fully-cascadable filter; universal voltage conveyor; UVC-N1C 0520; voltage-mode; active circuit; all-pass filter; dual-output; fully-cascadable filter; universal voltage conveyor; UVC-N1C 0520; voltage-mode